Um estudo sobre organização pedagógica na escola de tempo integral - Moraes da Costa, Antonia Flávia; Borges Figueiredo, Isadora; Nascimento Silva, Márcio César de; Moraes de Sousa, Helena do Carmo; França-Carvalho, Antonia Dalva (Epistemologia e Práxis Educativa - EPEduc, 2018)
.